Elevated CO2 increases photosynthesis in fluctuating irradiance regardless of photosynthetic induction state - Kaiser, Elias (Journal of experimental botany, 2017)
© The Author 2017. Published by Oxford University Press on behalf of the Society for Experimental Biology.